The Influence of Pore Porosity on Overpressure Formation: A Case Study of Field X, Kutai Basin - Dhiau Rahman Fikri; Abdul Haris; Rinaldo; Widi Atmoko (UIR PRESS, 2025)
The Kutai Basin is a region with complex geological characteristics, which complicate formation pressure prediction and pose drilling risks such as overpressure. This study aims to analyze the relationship between porosity and overpressure using well log data, including sonic (DT), resistivity (ILD), neutron porosity (NPHI), and density (RHOB) logs. Overpressure is calculated based on the difference between actual pore pressure and normal hydrostatic pressure, supported by vertical stress estimation. The analysis results indicate that overpressure zones occur within specific intervals, particularly in the Pulau Balang Formation, which is dominated by impermeable shale lithology. These overpressure zones are characterized by high DT values, low ILD readings, and sustained high porosity despite increasing depth. This suggests that the overpressure is caused by undercompaction (Disequilibrium compaction), where rapid sedimentation rates hinder the expulsion of pore fluids. A Dutta crossplot confirms the dominance of smectite minerals that have not yet transformed into illite, reinforcing the indication that the rocks have not undergone significant chemical compaction. The correlation between preserved porosity and overpressure zones provides critical information for mitigating drilling risks and optimizing reservoir development.